Concurrent development of encapsulating peritoneal sclerosis and calciphylaxis in a patient with peritoneal dialysis for end-stage renal disease. Issue 3 (23rd March 2022) - Win, Khine Myat; Castelhano, Rute; Dasgupta, Tanaji
Abstract : Both encapsulating peritoneal sclerosis (EPS) and calciphylaxis are rare but severe complications involving patients with end-stage renal disease. In this report, we discuss a unique case of a 73-year-old female patient who had undergone 8 years of peritoneal dialysis for IgA nephropathy and concurrently developed these two synchronous complications within 3 months of each other. Diagnosis and management of both conditions were discussed in detail as well as the possible association between the two. With surgical treatment for EPS and measures to minimise bone mineral disorder abnormalities, both complications have been successfully managed to date.